2017
DOI: 10.1159/000481943
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in Frailty among Older Adults: Results from a 10-Year Longitudinal Study in the Netherlands

Abstract: Background: Frailty is an important risk factor for adverse outcomes in older people. Substantial variation in frailty prevalence between socioeconomic groups exists, but longitudinal evidence for the association between socioeconomic position (SEP) and frailty is scarce. Objective: To investigate the course of socioeconomic inequalities in frailty among older adults during 10 years of follow-up. Methods: Data were used from the Longitudinal Aging Study Amsterdam (n = 1,509). Frailty was measured with the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
45
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 34 publications
11
45
1
2
Order By: Relevance
“…With regard to SES-based health gaps in frailty in older age, we found that the gap between low and high educated respondents did not converge with age but remained constant, which conforms to the results of previous longitudinal studies modelling single health outcomes such as self-reported health status or the number of chronic diseases [29][30][31] more generally -although diverging patterns have been reported with regard to functional limitations [29,30] and frailty (index) trajectories more specifically [6,[8][9][10]. In contrast to Hoogendijk et al [10], we found SES-related differences for both men and women. Our results thus support the status maintenance hypothesis [32].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…With regard to SES-based health gaps in frailty in older age, we found that the gap between low and high educated respondents did not converge with age but remained constant, which conforms to the results of previous longitudinal studies modelling single health outcomes such as self-reported health status or the number of chronic diseases [29][30][31] more generally -although diverging patterns have been reported with regard to functional limitations [29,30] and frailty (index) trajectories more specifically [6,[8][9][10]. In contrast to Hoogendijk et al [10], we found SES-related differences for both men and women. Our results thus support the status maintenance hypothesis [32].…”
Section: Discussionsupporting
confidence: 89%
“…Our results thus support the status maintenance hypothesis [32]. It can be argued that the educational level which is usually fixed in early life keeps the health gap up on the one hand due to differences in health knowledge and behaviour delaying the onset of health problems for the higher educated [33], as well as indirectly on the other hand through the effects of occupational position, income and wealth [6,8,10], which are co-determined by educational achievement, but were not included in the present study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This includes, for example, frailty and polypharmacy, which have shown to be more prevalent in older adults with low education or low levels of income (1)(2)(3). Another geriatric condition with serious consequences for older people in terms of quality of life and adverse health events is malnutrition (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Dependiendo del estudio, la prevalencia de este síndrome en adultos mayores de 65 años se sitúa entre un 4% y 50,1%, siendo muy variable entre las distintas series y aumentando con la edad (Gale, 2014) (Romero-Ortuno, 2014) (Clegg, 2013) (Theou, 2015) (Garcia-Garcia, 2011) (Abellán García, 2017), más frecuente en mujeres que en hombres y como mayor prevalencia en personas con menores niveles educacionales y salariales, peor salud y mayores tasas de comorbilidad y enfermedades crónicas (Hoogendijk, 2018).…”
Section: Figura 2 Determinantes Para El Envejecimiento Según Lalondeunclassified